2014
DOI: 10.1016/j.jmr.2014.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing skin effects in conductors with MRI: 7Li MRI experiments and calculations

Abstract: While experiments on metals have been performed since the early days of NMR (and DNP), the use of bulk metal is normally avoided. Instead, often powders have been used in combination with low fields, so that skin depth effects could be neglected. Another complicating factor of acquiring NMR spectra or MRI images of bulk metal is the strong signal dependence on the orientation between the sample and the radio frequency (RF) coil, leading to non-intuitive image distortions and inaccurate quantification. Such fac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(25 citation statements)
references
References 45 publications
1
24
0
Order By: Relevance
“…[12][13][14]17,[22][23][24] Interestingly, the 3d CSI sheds new light on previous bulk metal NMR studies. For instance, in an earlier study, 12 a similar shift difference between NMR peaks was observed at and ⊥ orientations (relative to B 0 ) of the major faces of a thinner metal strip, by carrying out two separate experiments.…”
Section: Csimentioning
confidence: 89%
See 4 more Smart Citations
“…[12][13][14]17,[22][23][24] Interestingly, the 3d CSI sheds new light on previous bulk metal NMR studies. For instance, in an earlier study, 12 a similar shift difference between NMR peaks was observed at and ⊥ orientations (relative to B 0 ) of the major faces of a thinner metal strip, by carrying out two separate experiments.…”
Section: Csimentioning
confidence: 89%
“…Moreover, the analysis presented here may throw light on previous bulk metal MRI studies. For instance, consider the MRI in orientation in an earlier study: 14 with c = 10mm and ∆y = 31µm, Eq. (5) yields S ac /S ab = 161, rendering the contribution from the ab faces all but invisible in those images.…”
Section: Intensity Ratio Formulae For Bulk Metal Mri and Csimentioning
confidence: 99%
See 3 more Smart Citations